A new species of the genus Indotrichius Krikken, 2009 from Southern Vietnam (Coleoptera: Scarabaeidae, Cetoniinae) - Ricchiardi, Enrico (Fragmenta entomologica, 2017)
Four species of Trichiina from the Himalayas and adjacent regions were up till now associated with the genus Indotrichius Krikken, 2009. Surprisingly, a new species, here described, was collected in the province of Lam Dong, in the south of Vietnam, considerably expanding the distribution range of Indotrichius. The genus is shortly re-diagnosed and a list of species is given.